The effect of levofloxacin on the lung microbiota of laboratory rats. (9th August 2019) - Finn, Sade M. B.; Scheuermann, Uwe; Holzknecht, Zoie E.; Gao, Qimeng; Ibrahim, Mohamed M.; Parker, William; Granek, Joshua a.; Lin, Shu S.; McKenney, Erin a.; Barbas, Andrew S.
Abstract: Aim: The aim of this study was to investigate the short-term effect of levofloxacin on the microbiota of healthy lungs. Material and methods: Male F344 rats received either no levofloxacin (n = 9), intravenous levofloxacin (n = 12), oral levofloxacin (n = 12), or subcutaneous levofloxacin (n = 14). Rats received a clinically applicable dose (5.56 mg/kg) of levofloxacin via the assigned delivery route once daily for three days. On day four, lung tissue was collected and the lung microbiota composition was investigated using 16S ribosomal RNA gene sequencing. Results: Untreated lungs showed a microbiota dominated by bacteria of the genera Serratia . After treatment with levofloxacin, bacteria of the genus Pantoea dominated the lung microbiota. This was observed for all routes of antibiotic administration, with a significant difference compared to no-antibiotic control group (PERMANOVA: P < 0.001; homogeneity of dispersions: P = 0.656). Conclusion: Our study is the first to demonstrate the effects of levofloxacin therapy on lung microbiota in laboratory rats. Levofloxacin treatment by any route of administration leads to profound changes in the rat lung microbiota, resulting in the predominance of bacteria belonging to the genus Pantoea . Further studies regarding the role of long-term application of broad spectrum antibiotics on induction of lung, allergic and autoimmune diseases are indicated. Abbreviations: ASVs: Amplicon sequence variants; F344: Fischer 344; IV: Intravenous; NMDS: Non-metric multidimensional scaling; OTU: Operational taxonomic unit; PERMANOVA: Permutational multivariate analysis of variance; Subq: Subcutaneous.